Analisis M-Banking Service Quality Terhadap Kepuasan Nasabah yang Berdampak pada Loyalitas Nasabah pada PT. Bank Rakyat Indonesia, Tbk - Fadilah Nur Achzuhra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Bank Rakyat Indonesia (BRI) is a state-owned bank (BUMN) that has customers spread throughout Indonesia, from big cities to remote villages. The problem that has occurred at Bank BRI lately is that there are still customers who are dissatisfied and there are complaints about the m-banking service on the BRImo application launched by Bank BRI. The purpose of this study is to analyze the quality of m-banking services based on customer satisfaction and complaints at Bank BRI work units on the BRImo m-banking application, to determine the effect of M-Banking Service Quality on customer loyalty through customer satisfaction on the BRImo m-banking application, to determine the effect of customer satisfaction on customer loyalty on the BRImo m-banking application, and to determine the impact on customer loyalty based on the effect of M-Banking Service Quality on customer satisfaction. The research method used in this study is a quantitative method by distributing questionnaires and collecting secondary data. In order for the research objectives to be met, calculations were carried out using the simple linear regression analysis method. The dimensions used for testing simple linear regression are the dimensions of M-Banking Service Quality. The dimensions of M-Banking Service Quality consist of convenience, security, ease, design and application system.